IMPROVING THE METHODOLOGICAL TRAINING OF FUTURE PRIMARY SCHOOL TEACHERS (Academicia Globe: Inderscience Research, 2023)
The article discusses the improvement of training programs for future teachers in primary grades. Innovative approaches to improving the methodical training of primary school teachers are analyzed.